Strategi Menghidupkan Motivasi Belajar Siswa Sekolah Dasar di Masa Pandemi Covid-19 Melalui Kelompok Belajar - Amirudin Amirudin; Supriyatin Supriyatin; Sylvia Dewi; Yuli Ismeliantika (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2021)
This study aims to determine strategies in increasing student learning motivation to maintain the continuity of the educational process in the Study From Home (SFH) policy during the COVID-19 pandemic. The approach used in this research is qualitative with the research subject, namely students in the study group in Jungjang village. Data collection techniques used were interviews and documentation. The results showed that the form of the learning group teacher strategy to increase student learning motivation in the SFH policy in the midst of the COVID-19 outbreak was with student work study groups which were proven to increase student learning motivation. The obstacles encountered by the learning group teacher were related to the aspects of the students' parents, learning facilities, and the creativity of the learning group teachers. The benefits of this research are the growth of student motivation, train student discipline, and help improve the closeness between parents and children. ABSTRAK Penelitian ini bertujuan untuk Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dengan subjek penelitian yaitu siswa kelompok belajar di desa Jungjang. Teknik pengumpulan data yang digunakan adalah wawancara serta dokumentasi. Hasil penelitian menunjukkan bahwa bentuk strategi guru kelompok belajar untuk meningkatkan motivasi belajar siswa dalam kebijakan SFH di tengah wabah COVID-19 adalah dengan kelompok belajar kerja tugas siswa yang terbukti dapat meningkatkan motivasi belajar siswa. Hambatan yang ditemui guru kelompok belajar yaitu berkenaan dengan aspek orang tua peserta didik, sarana pembelajaran, dan kreativitas guru kelompok belajar. Adapaun manfaat dari penelitian ini adalah tumbuhnya motivasi belajar siswa, melatih kedisiplinan siswa, serta membantu meningkatkan kedekatan antara orangtua dan anak.